Low-frequency, threatened habitats drive the large-scale distribution of Andean Condors in southern Patagonia - Pérez García, Juan M. (2018)
The analysis of factors that determine the distribution of top-scavengers at large scales can provide clues to understanding important ecological processes and may be useful in establishing conservation and management strategies. Here, we conducted a large-scale survey to study the distribution of the threatened Andean Condor Vultur gryphus in relation to environmental factors in southern Patagonia. This area has undergone the settlement of livestock and the introduction of exotic wildlife, although to a lesser extent than in the distribution of Condors in northern Patagonia. The aim of this study was to determine the relevance of different factors such as the availability of food resources, the availability of suitable nesting and roosting places and the presence of humans on large-scale condor distribution. Our results show that the presence of meadows was the primary factor shaping Andean Condor distribution, despite the fact that this habitat occupies only 4% of the Patagonian landscapes. However, this habitat has a high probability of herbivore presence, so Condors seem to optimize their searching. The availability of nesting and roosting cliffs also contributed to explaining the observed distributions. Our results suggest that Condor distribution in southern Patagonia is a compromise between the spatial locations of two low-frequency habitats – meadows and cliffs. A successful Condor conservation strategy in southern Patagonia should include the protection of these habitats and the regulation of farming expansion, including the recovery of meadows.